Effect of warm water compress with endorphin massage on reducing labor pain intensity in the first stage active phase - Sumartila; Palimbo, Adriana; Istiqamah; Mahdiyah, Dede (Ananda - Health & Education Foundation, 2024)
Background: Pain during childbirth is subjective and influenced by various factors, including psychosocial factors, habits and women’s perception of the meaning of childbirth. Uncontrolled labor can harm the mother and fetus. Excessive pain increases anxiety and restlessness in pregnant women, causing increased catecholamine secretion. Non-pharmacological complementary therapy techniques will be used to reduce labor pain. Objective: To determine the effect of warm water compresses with endorphin massage on reducing labor pain intensity during the first stage active phase. Method: This type of quantitative research is a one-group pretest-posttest design with 15 mothers in the first stage of labor as participants, obtained using total sampling. Warm water compress and endorphin massage are performed simultaneously for 20 minutes. Labor pain data was collected using the Wong Baker Faces Scale instrument. Non-parametric statistical analysis using the Wilcoxon sign rank test. Results: The characteristics of the 15 respondents include 11 people (73.3%), 11 people (73.3%), seven people (46.7%), 10 people (66.7%), 10 people in the multiparity category, and 13 people in the 20-35 year age category (86.7%). The results of the Wilcoxon sign rank test showed that giving a warm water compress combined with endorphin massage had a significant effect (p-value <0.05) on reducing the intensity of labor pain in the first active phase. Conclusion: Warm water compresses combined with endorphin massage showed a positive influence in managing the intensity of the pain scale in the first stage of labor